LCC (Local Coordinating Council) Candidate Interviews (1976)
This document outlines the format and schedule for the May 12, 1976 LCC (Local Coordinating Council) Candidate Interviews, where candidates for the 36th Assembly District and several supervisorial races were each given 15 minutes to speak and answer audience questions. Jane Tolmach, Charles Imbrecht, Pete Bokron, and other candidates were listed with specific time slots, and Ken MacDonald was noted as unable to attend. Candidates were also required to complete a questionnaire addressing public employee strikes, binding arbitration, tax limits (SB 90), seniority, budget priorities, and major local development issues such as a third community college, an LNG plant in Hueneme, highways, strip mining, and a commercial airport. The event was organized in cooperation with the Public Employees Association of Ventura County, and completed questionnaires were made available for public review.